2015
DOI: 10.1007/s13353-015-0299-0
|View full text |Cite
|
Sign up to set email alerts
|

Case–control approach application for finding a relationship between candidate genes and clinical mastitis in Holstein dairy cattle

Abstract: Mastitis is a major source of economic loss in dairy herds. The objective of this research was to evaluate the association between genotypes within SLC11A1 and CXCR1 candidate genes and clinical mastitis in Holstein dairy cattle using the selective genotyping method. The data set contained clinical mastitis records of 3,823 Holstein cows from two Holstein dairy herds located in two different regions in Iran. Data included the number of cases of clinical mastitis per lactation. Selective genotyping was based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 27 publications
0
10
1
Order By: Relevance
“…Differences in EBVs for production traits when comparing the heterozygous genotype to both homozygous genotypes of SLC11A1 SNP are given in Table 1. In spite of the positive significant effect of SLC11A1 gene on clinical mastitis resistance, which has been previously shown (BAGHERI et al, 2016), no significant relation was found between this gene and production traits (protein and fat yield and protein and fat percentage). It should be kept in mind that selection of specific alleles of important genes may improve udder health; however, correlated response for other economic traits should not be ignored.…”
Section: Resultscontrasting
confidence: 62%
See 3 more Smart Citations
“…Differences in EBVs for production traits when comparing the heterozygous genotype to both homozygous genotypes of SLC11A1 SNP are given in Table 1. In spite of the positive significant effect of SLC11A1 gene on clinical mastitis resistance, which has been previously shown (BAGHERI et al, 2016), no significant relation was found between this gene and production traits (protein and fat yield and protein and fat percentage). It should be kept in mind that selection of specific alleles of important genes may improve udder health; however, correlated response for other economic traits should not be ignored.…”
Section: Resultscontrasting
confidence: 62%
“…Polymerase chain reaction-mediated single strand conformation polymorphism (PCR-SSCP) results showed a polymorphism due to a mutation at position 1139 (NM_174652.2:c.1139 C > G). More information on SSCP variants has been presented in BAGHERI et al (2016). Differences in EBVs for production traits when comparing the heterozygous genotype to both homozygous genotypes of SLC11A1 SNP are given in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Over the past decade, some reports in the literature have described a strong association between polymorphisms in the bovine CXCR1 gene and pathogen-specific incidence rate of clinical mastitis (VERBEKE et al, 2014;PAWLIK et al, 2015;BAGHERI et al, 2016). Recently, Pokorska et al (2016) identified single nucleotide polymorphisms located within the coding region and the 3'UTR site of the bovine CXCR1 gene that were significantly associated with the susceptibility of cows to clinical mastitis.…”
Section: Introductionmentioning
confidence: 99%